2012
DOI: 10.1007/s10198-012-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

Does the US health care safety net discourage private insurance coverage?

Abstract: The large and growing uninsured population poses an alarming threat to the US health care system, and is a major target of the Obama health reform. This paper investigates analytically and empirically the degree to which the absence of health insurance in the US reflects the availability of the health care safety net, such as the guaranteed or charitable care provided by emergency rooms, community health centers and physicians. Our theoretical model demonstrates that the safety net can be a real alternative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Addressing health inequalities in Argentina is important due to the high proportion of older, particularly socially disadvantaged adults. These are, largely, more likely to benefit from both social policies leading to improvements in the welfare state (Qin & Liu, 2013) and reduction in socioeconomic inequalities (Stuckler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing health inequalities in Argentina is important due to the high proportion of older, particularly socially disadvantaged adults. These are, largely, more likely to benefit from both social policies leading to improvements in the welfare state (Qin & Liu, 2013) and reduction in socioeconomic inequalities (Stuckler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is controversy on the impact of insurance coverage on health outcomes and health disparities in Colombia, 3,69,13 the United States, 1,2,10,32 and elsewhere. 3336 Although some studies have suggested that the subsidized scheme led to improvements in maternal and children’s health, 6 little is known about impact on adult outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1 People with lower socioeconomic status are at increased risk of many conditions and are therefore more likely to benefit from an expansion in health insurance coverage. 1 Previous observational studies in the United States have suggested that a lack of health insurance was associated with an increased risk of subsequent mortality in all socioeconomic groups. 2 However, little is known about the impact of health insurance coverage on socioeconomic disparities in mortality following a major expansion in insurance coverage.…”
mentioning
confidence: 99%
“…Blumberg et al used the 1990 SIPP to show that, of those children made eligible by expansions, only 4% as many lost private coverage as gained public coverage, providing an insignificant crowd‐out. Xuezheng Qin combined 3 risk‐undertaking tools: social safety net, self‐insurance, and private insurance into an expected utility framework—Consumer Insurance Demand Model. Under specific conditions, the size of social safety may reduce the probability of individual insurance purchase partly or even thoroughly.…”
Section: Literature Reviewmentioning
confidence: 99%